Protist communities of microbial mats from the extreme environments of five saline Andean lagoons at high altitudes in the Atacama Desert - Acosta, Eduardo; Nitsche, Frank; Dorador, Cristina; Arndt, Hartmut (Frontiers in Microbiology, 2024)
Introduction Heterotrophic protists colonizing microbial mats have received little attention over the last few years, despite their importance in microbial food webs. A significant challenge originates from the fact that many protists remain uncultivable and their functions remain poorly understood. Methods Metabarcoding studies of protists in microbial mats across high-altitude lagoons of different salinities (4.3–34 practical salinity units) were carried out to provide insights into their vertical stratification at the millimeter scale. DNA and cDNA were analyzed for selected stations. Results Sequence variants classified as the amoeboid rhizarian Rhogostoma and the ciliate Euplotes were found to be common members of the heterotrophic protist communities. They were accompanied by diatoms and kinetoplastids. Correlation analyses point to the salinity of the water column as a main driver influencing the structure of the protist communities at the five studied microbial mats. The active part of the protist communities was detected to be higher at lower salinities (<20 practical salinity units). Discussion We found a restricted overlap of the protist community between the different microbial mats indicating the uniqueness of these different aquatic habitats. On the other hand, the dominating genotypes present in metabarcoding were similar and could be isolated and sequenced in comparative studies (Rhogostoma, Euplotes, Neobodo). Our results provide a snapshot of the unculturable protist diversity thriving the benthic zone of five athalossohaline lagoons across the Andean plateau.